IMPLEMENTASI ASUHAN KEPERAWATAN PEKA BUDAYA PADA KLIEN HIV DAN AIDS DI ERA PANDEMI COVID-19 - Maria Syelvrida Tumina; Agung Waluyo; Orpa Diana Suek (JURNAL KEPERAWATAN, 2024)
Introduction: The Covid-19 pandemic has impacted on the management of HIV and AIDS infections. The most sensed impactis related to the distribution and adequacy of ARVs. Factors that contribute to HIV care and services include access restrictions which result in ARV limitations that affect the physical and psychological health of patients. Assessment data found that patients and families were generally concerned about how to maintain medication adherence, hence becomes important in order to suppress infections and improve the patient's quality of life. Objectives: The purpose of this paper is to know the implementation of culturally sensitive nursing care to increase compliance during the Covid-19 pandemic. Method: The method used is a literature review taken from an online database which is limited to 2020-2021. The search resulted in obtaining 10 articles and further screening was carried out and 2 articles were found as main journals. Results: Culturally sensitive assessments can help plan interventions involving families and collaboration between professions. Implementation carried out includes preventing the spread of opportunistic infections, educating patients and families, compliance with taking medication, avoiding risky behavior and motivating patients to increase their knowledge. Conclusion: The role of nurses in providing culturally sensitive nursing care can help maintain care for patients living with HIV and AIDS, especially in the era of the Covid-19 pandemic, as an effort to maintain biological, psychological, social and spiritual health. Keywords: ARVs, adherence, Covid-19 pandemic, cultural sensitivity